2012
DOI: 10.1111/j.1365-2362.2012.02661.x
|View full text |Cite
|
Sign up to set email alerts
|

Pravastatin and simvastatin improves acetylsalicylic acid‐mediated in vitro blood platelet inhibition

Abstract: Our results suggested that statins may directly interact with platelet membranes or may modulate a signalling pathway in platelets (the pleiotropic effects of statins). It is possible that the statin effect on CD36 and ASA-mediated protein acetylation can be reached by the modulation of a distribution or a function of membrane-associated proteins. Further studies are certainly needed to better elucidate the mechanism(s) underlying the statins' effects on platelet sensitivity to ASA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…37 Statins also improve platelet reactivity in vitro. 38 Treatment of coronary risk factors by optimal medications, with subsequent improvement of endothelial dysfunction, could attenuate enhanced platelet aggregation and reduce cardiovascular events after PCI; however, the clinical evidence is not strong enough at present, and further investigation is encouraged. The precise molecular mechanism of endothelial dysfunction in patients with high RPR after DAPT remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…37 Statins also improve platelet reactivity in vitro. 38 Treatment of coronary risk factors by optimal medications, with subsequent improvement of endothelial dysfunction, could attenuate enhanced platelet aggregation and reduce cardiovascular events after PCI; however, the clinical evidence is not strong enough at present, and further investigation is encouraged. The precise molecular mechanism of endothelial dysfunction in patients with high RPR after DAPT remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…PRV is commercialized generically following the Bristol-Myers Squibb's patent expiration in April 2006 [7] under several brands in solid formulations containing 10, 20, 40 and 80 mg of active pharmaceutical ingredient. Other studies reveals that PRV stimulates angiogenesis in murine models [8] and improves acetylsalicylic acidmediated blood platelet inhibition, in vitro [9], while it has been suggested that statins appear to have therapeutic benefits in diseases that are unrelated to elevated serum cholesterol levels, such as pain and inflammation [10]. The importance of PRV active substance and statins is also revealed by review studies that indicate new therapeutic perspectives of statins in autoimmune diseases and cancer, antiatherosclerotic, anti-inflammatory, antioxidant, immunomodulatory and antithrombotic effects [11].…”
Section: Introductionmentioning
confidence: 99%
“…Early statin therapy has been shown to acutely affect platelet deposition following vascular injury by reducing granule secretion and thromboxane A 2 release, by nearly 30% [15]. In addition, statins may accentuate the inhibitory effect of aspirin on platelet aggregation [16].…”
Section: Evidence That Statins Have An Early Ef-fect On Platelets Andmentioning
confidence: 99%
“…In MIRACL, 3086 participants were randomized to receive high dose atorvastatin (80mg) within 1-4 days of presentation versus placebo. The primary endpoint of death, MI, and recurrent symptomatic myocardial ischemia at 16 Evidence of an acute benefit of statin therapy was observed in the ARMYDA-ACS (Atorvastatin for Reduction of Myocardial Damage during Angioplasty) study. As with MIRACL, the trial studied high-dose atorvastatin (80 mg) in a much smaller population of 171 patients.…”
Section: Early Clinical Response To Statins In Acute Coronary Syndromesmentioning
confidence: 99%